A guide to cranial nerve testing for musculoskeletal clinicians. (2nd November 2021) - Taylor, Alan; Mourad, Firas; Kerry, Roger; Hutting, Nathan
ABSTRACT: Background: Neurological examination in musculoskeletal practice is a key element of safe and appropriate orthopedic clinical practice. With physiotherapists currently positioning themselves as advanced first line practitioners, it is essential that those who treat patients who present with neck/head/orofacial pain and associated symptoms, should have an index of suspicion of cranial nerve (CN) dysfunction. They should be able to examine and determine if CN dysfunction is present, and make appropriate clinical decisions based upon those findings. Methods: This paper summarizes the functions, potential impairments of the nerves, associated conditions, and basic skills involved in cranial nerve examination. Results: A summary of cranial nerve examination is provided, which is based on the function of the nerves,  This is intended to facilitate clinicians to feel more confident at understanding neural function/impairment, as well as performing and interpreting the examination. Conclusion: This paper illustrates that CN testing can be performed quickly, efficiently and without the need for complicated or potentially unavailable equipment. An understanding of the CN's function and potential reasons for impairment is likely to increase the frequency of CN testing in orthopedic clinical practice and referral if positive findings are encountered.